Mother tongue and English language: a power struggle - Ariffin, Adlina (USIM Press (Universiti Sains Islam Malaysia), 2015)
The purpose of this paper is to highlight the conflict of two languages, one being the mother tongue of a country and the other a second language of a country i.e. Bahasa Melayu and English language, in the process of empowering the society with knowledge in order to stay competitive in this challenging and ever-changing world. In so doing, the paper attempts to describe the evolutionary nature of languages to remain relevant today and in the future. It draws attention to the importance of mother tongue and English language in seeking knowledge and also the polemic that has resulted when both languages are pitted against each other. Thus, the question then is “How should the mother tongue i.e. Bahasa Melayu remain pertinent as a language of knowledge in Malaysia?”and “What is the role of English language in the knowledge seeking process?” . This paper will also shed some light on the importance of language planning in maintaining an equilibrium between a mother tongue and a foreign language.